Parental Morality and the Morality of Generation Z Adolescents: A Mixed Methods Research - Medez, Sharon Rose; Gayoles, Lisa Anna (Technium Social Sciences Journal, 2021)
Parents’ behavior, attitudes and beliefs greatly impact their children’s development. Parents play a crucial role in the moral development of their children. This study aims to explore, describe, and interpret the lived experiences of parents and their Gen Z adolescent children regarding morality. This study also aims to determine the relationship between parental morality and the morality of their Gen Z adolescent children. It utilized the mixed methods research design, specifically the phenomenological research design and the correlational research design. Fifty-two high school students of a private school and their parents participated in the study. Students are between ages 13 and 16 years. This study utilized the Moral Authority Scale (MAS-R) to measure parental and adolescent morality. Common themes for the lived experiences of the parents and their Gen Z adolescent children are: parents are dispensers of values, obedience to parents, listening to a friend’s opinion, showing concern for others, treat everybody equally, and the law over self-interest. The results of the study revealed that the morality of both parents and the morality of their adolescent children was predominantly the Principle Morality, specifically the Equality Source. There is no significant relationship between parental morality and the morality of their adolescents, although the father’s morality appears to have more influence on their adolescent children’s morality. The findings suggest implications in family strengthening programs utilizing parent education and parent training.